A Systematic Review on The Insurability Risk for Long-Term Care Insurance in Europe and Asia Countries - Nurin Amni Arshad; Mazlynda Md Yusuf (USIM Press, 2024)
MJoSHT2020, Volume 7, Special Issue, eISSN: 2601-0003